Diario social di un Rettore 3 Scrivendo appunti diversi - Dei, Luigi (Libere carte, 2018)
«Chemistry and fantasy, art and science, photography and music, education and play, technology and communicative desire, civic passion and didactic commitment did not formerly (or not only) create a nicely original and bizarre mixture, but rather a very original score, which invites you to reflect on the operation of objects looking trivial despite not being such; this makes us gaze into the depth of common things and shows them to us in a way which leads us to feel as if we saw them for the first time. The secret lies in the pen of a light-handed writer, a scientist-poet who is a school man and enthusiastically manages to weld inventive energy and scientific expertise together. The opportunity is not to be missed, because a new contact with the world can bring forth new emotions, new thoughts, new feelings. A light hand smudged with plaster »(Gino Tellini).